Working Memory Has Better Fidelity Than Long-Term Memory: The Fidelity Constraint Is Not a General Property of Memory After All. (February 2019) - Biderman, Natalie; Luria, Roy; Teodorescu, Andrei R.; Hajaj, Ron; Goshen-Gottstein, Yonatan
How detailed are long-term-memory representations compared with working memory representations? Recent research has found an equal fidelity bound for both memory systems, suggesting a novel general constraint on memory. Here, we assessed the replicability of this discovery. Participants (total N = 72) were presented with colored real-life objects and were asked to recall the colors using a continuous color wheel. Deviations from study colors were modeled to generate two estimates of color memory: the variability of remembered colors—fidelity—and the probability of forgetting the color. Estimating model parameters using both maximum-likelihood estimation and Bayesian hierarchical modeling, we found that working memory had better fidelity than long-term memory (Experiments 1 and 2). Furthermore, within each system, fidelity worsened as a function of time-correlated mechanisms (Experiments 2 and 3). We conclude that fidelity is subject to decline across and within memory systems. Thus, the justification for a general fidelity constraint in memory does not seem to be valid.